Hostility, compassion and role reversal in West Virginia's long opioid overdose emergency - Jeff Ondocsin; Sarah G. Mars; Mary Howe; Daniel Ciccarone (BMC, 2020)
Abstract Background West Virginia is a largely rural state with strong ties of kinship, mutual systems of support and charitable giving. At the same time, wealth inequalities are extreme and the state's drug overdose fatality rate stands above all others in the USA at 51.5/100,000 in 2018, largely opioid-related. In recent years, harm reduction services have been active in the state but in 2018 Charleston's needle and syringe program was forced to close. This paper considers the risk environment in which the state's drug-related loss of life, and those attempting to prevent it, exist. Methods This rapid ethnographic study involved semi-structured interviews (n = 21), observation and video recordings of injection sequences (n = 5), initially recruiting people who inject heroin/fentanyl (PWIH) at the Charleston needle and syringe program. Snowball sampling led the research team to surrounding towns in southern West Virginia. Telephone interviews (n = 2) with individuals involved in service provision were also carried out. Results PWIH in southern West Virginia described an often unsupportive, at times hostile risk environment that may increase the risk of overdose fatalities. Negative experiences, including from some emergency responders, and fears of punitive legal consequences from calling these services may deter PWIH from seeking essential help. Compassion fatigue and burnout may play a part in this, along with resentment regarding high demands placed by the overdose crisis on impoverished state resources. We also found low levels of knowledge about safe injection practices among PWIH. Conclusions Hostility faced by PWIH may increase their risk of overdose fatalities, injection-related injury and the risk of HIV and hepatitis C transmission by deterring help-seeking and limiting the range of harm reduction services provided locally. Greater provision of overdose prevention education and naloxone for peer distribution could help PWIH to reverse overdoses while alleviating the burden on emergency services. Although essential for reducing mortality, measures that address drug use alone are not enough to safeguard longer-term public health. The new wave of psychostimulant-related deaths underline the urgency of addressing the deeper causes that feed high-risk patterns of drug use beyond drugs and drug use.